Socio-demographic risk factors associated with febrile seizures at Puducherry: a retrospective study - ., Gobinaath; J., Arun Daniel (International Journal of Contemporary Pediatrics, 2020)
Background: Febrile seizures occur commonly in the under 5 age group and is associated with few risk factors causing its recurrence like very high fever, family history of seizures, low sodium levels and younger age of onset which are subject to seasonal and wide geographical variations. This study aimed at detecting the major risk factors associated with recurrent febrile seizures in an Indian population. Methods: A retrospective hospital-based study was conducted among a total of 300 cases aged 6 months to 5 years attending to the paediatric OPD with history of fever followed by febrile seizures. Information regarding socio-demographic and clinical variables associated with febrile seizure was collected and analyzed. Results: The mean age of the study participants was 25.6±2.2 months and majority (60%) were males. Family history of seizures was present in 25.3% (n=76) of the children with febrile seizures. Respiratory infections (73.3%) and gastroenteritis (17%) were the major infective reasons associated with the occurrence of febrile seizures followed by pneumonia (6.3%) and urinary tract infections (5%). Recurrence of FS was significantly higher among the children with family history of FS (p=0.009), age at onset lesser (p<0.001) and simple FS seizures. Conclusions: Younger age at onset and positive family history of seizures were important socio-demographic risk factors associated with recurrent febrile seizures.